Effect of boric acid on some elemental levels on rat’s liver and kidney tissues during mercury chloride exposure - Akkoyun, Hurrem Turan (Cellular and Molecular Biology, 2018)
In this study, the effect of boric acid on the important trace elements copper (Cu), iron (Fe), zinc (Zn), manganese (Mn) and nickel (Ni) in liver and kidney tissue of rats treated with mercury chloride was investigated. Twenty-four male Wistar albino rats (weighing 200 ± 300 g) were divided into 3 groups: Control (C), Mercury chloride (HgCl2), Mercury chloride (HgCl2) + boric acid (BA). Iron and copper were decreased whereas Mn, Zn and Ni levels were increased in liver tissue in Hg administered group compared to control. Cu (p<0.01) and Mn (p<0.001) levels were increased in Hg + BA administered group compared to Hg group. Renal tissue Cu (p<0.01), Mn and Zn levels were increased whereas Ni (p<0.05) and Fe levels were decreased in Hg administered group compared to control group. Cu (p<0.001) and Zn (p<0.05) content increased in Hg + BA group compared to control group. As a result, it is thought that boric acid may have an effect on important trace element levels such as copper (Cu), iron (Fe), zinc (Zn), manganese (Mn), nickel (Ni) in case of oxidative stress caused by mercury chloride.